In silico promoter analysis and functional validation identify CmZFH, the co-regulator of hypoxia-responsive genes CmScylla and CmLPCAT. (January 2022) - He, Li; Chen, Ivy W.; Zhang, Zan; Zheng, Wenping; Sayadi, Ahmed; Wang, Lei; Sang, Wen; Ji, Rui; Lei, Jiaxin; Arnqvist, Göran; Lei, Chaoliang; Zhu-Salzman, Keyan
Abstract: Oxygen (O2 ) plays an essential role in aerobic organisms including terrestrial insects. Under hypoxic stress, the cowpea bruchid ( Callosobruchus maculatus ) ceases feeding and growth. However, larvae, particularly 4th instar larvae exhibit very high tolerance to hypoxia and can recover normal growth once brought to normoxia. To better understand the molecular mechanism that enables insects to cope with low O2 stress, we performed RNA-seq to distinguish hypoxia-responsive genes in midguts and subsequently identified potential common cis -elements in promoters of hypoxia-induced and -repressed genes, respectively. Selected elements were subjected to gel-shift and transient transfection assays to confirm their cis -regulatory function. Of these putative common cis -elements, AREB6 appeared to regulate the expression of CmLPCAT and CmScylla, two hypoxia-induced genes. CmZFH, the putative AREB6 -binding protein, was hypoxia-inducible. Transient expression of CmZFH in Drosophila S2 cells activated CmLPCAT and CmScylla, and their induction was likely through interaction of CmZFH with AREB6. Binding to AREB6 was further confirmed by bacterially expressed CmZFH recombinant protein. Deletion analyses indicated that the N-terminal zinc-finger cluster of CmZFH was the key AREB6- binding domain. Through in silico and experimental exploration, we discovered novel transcriptional regulatory components associated with gene expression dynamics under hypoxia that facilitated insect survival. Graphical abstract: Image 1 Highlights: Transcriptomic analysis identified 602 hypoxia-responsive genes. Common cis -elements were found in hypoxia-induced and -repressed genes, respectively. AREB6 had cis -regulatory role in CmScylla and CmLPCAT expression. Hypoxia-induced CmZFH bound to AREB6 to activate gene expression. CmZFH interacted with AREB6 via its N-terminal zinc-finger cluster.